Entangled Worlds : Religion, Science, and New Materialisms - Keller, Catherine (Book collections on Project MUSE., 2017)
This collection examines the intersections of religion and ""new"" materialisms. Calling upon an interdisciplinary throng of scholars in science studies, religious studies, and theology, it assembles a multiplicity of experimental perspectives on materiality: what is matter, how does it materialize, and what sort of worlds are enacted in its varied entanglements with divinity?